TINJAUAN HUKUM ISLAM TERHADAP PENGGUNAAN ALAT KONTRASEPSI SUNTIK TIGA BULAN : STUDI KASUS DI DESA SAMARENDA KABUPATEN MOROWALI - risnawati (Program Studi Perbandingan Mazhab, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2021)
This paper discusses the Islamic Law Review Against the Use of Three-Month Injectable Contraceptive Devices (Case Study in Samarenda Village, Morowali Regency) which is the object of this research is Islamic law on the use of three-month injectable contraceptives in Samarenda Village, Morowali Regency. The method that the author uses in this paper is a qualitative research method. The results showed that 1). Some of the factors that cause a married couple in Samarenda Village to use contraceptives, including first, because the number of children they have is in accordance with what they want so that they no longer want to add children, both methods are easy to use and have a good level of effectiveness. , thirdly because of the factor of having had bad experiences with previous contraceptives, and fourthly because of economic factors. 2). The view of Islamic law on the use of three-month injectable contraceptives in Samarenda Village, Morowali Regency is not in accordance with Islamic law because it looks at the factors that cause them to use these contraceptives and the reasons they choose to limit the birth rate of children in the family, while in Islam allow the use of contraception to space births.